Diagnosis of Biofilm-Associated Peri-Implant Disease Using a Fluorescence-Based Approach - Geelsu Hwang; Markus B. Blatz; Mark S. Wolff; Liviu Steier (MDPI AG, 2021)
Dental implants have become a routine component of daily dental practice and the demand for dental implants is expected to increase significantly in the future. Despite the high success rates of dental implants, failures do occur, resulting in discomfort, rampant destruction of the oral health, or painful and costly surgical replacement of a failed implant. Peri-implant diseases are inflammatory conditions affecting the soft/hard tissues surrounding a functional dental implant. Plenty of experimental evidence indicates that the accumulation of dental plaque at the soft tissue-implant interface and the subsequent local inflammatory response seems to be key in the pathogenesis of the peri-implant mucositis. Such peri-implant-soft tissue interface is less effective than natural teeth in resisting bacterial invasion, enhancing vulnerability to subsequent peri-implant disease. Furthermore, in certain individuals, it will progress to peri-implantitis, resulting in alveolar bone loss and implant failure. Although early diagnosis and accurate identification of risk factors are extremely important to effectively prevent peri-implant diseases, current systematic reviews revealed that a uniform classification and diagnostic methodology for peri-implantitis are lacking. Recent progress on fluorescence-based technology enabled rapid diagnosis of the disease and effective removal of plaques. Here, we briefly review biofilm-associated peri-implant diseases and propose a fluorescence-based approach for more accurate and objective diagnoses. A fluorescence-based diagnosis tool through headlights combined with special-filtered dental loupes may serve as a hands-free solution for both precise diagnosis and effective removal of plaque-biofilms.